Employing innovative evidence-backed community processes for maternal health services by Dalit women - Sathyasree Goswami; Edward Premdas Pinto (BMC, 2022)
Abstract Background Health care services express social and structural inequalities, especially for Dalits and women, due to the indignity and discrimination experienced in health care facilities. Jagrutha Mahila Sanghatane (JMS), a grass-roots organization led by neo-literate Dalit women in rural Karnataka in India, adopted a human rights-based social accountability (SA) approach to address discrimination and dignity in accessing maternal health services. This approach integrated community-based evidence with multi-pronged and multi-level accountability processes with their goal of socio-political empowerment. Methods The methodological approach is qualitative and uses document analysis, including thematic and content analysis, in-depth group discussions with the campaign leaders, participant observation and interviews with the community health workers. Results JMS embedded the practice and processes of SA in the politics of empowerment which was central to addressing the structural issues of discrimination and social exclusion faced by Dalit women. The human rights perspective and the pathway of conscientize-organize-struggle provided by the Dalit liberation leader, Dr B. R. Ambedkar, facilitated the organization to conceptualize SA as a process of claiming dignity and justice for Dalit women. Integrating the evidence generation and its deployment into the community campaign cycles, Dalit women could use the accountability process for intensifying mobilization and empowerment. The cumulative impact of the community enquiry relentlessly pursued through the framework of a campaign brought changes in several aspects of primary health care and specific dimensions of maternal health care. Community ownership of the SA process, participation and empowerment were integral to the generation, synthesis and deploying of evidence. Deploying evidence in multiple forms, both horizontally with the communities and vertically with the authorities deepened communities' mobilization and intensified Dalit women's negotiating power with the authorities. The iterative and persistent process of SA provides insights into re-articulating SA beyond the usual recognition of outputs such as report cards into the politics of meaning-making by the mobilized community of the marginalized. The community-based organization posited the SA itself as the process of resistance to structural injustice and as an avenue or their empowerment. Conclusions For marginalized communities, the SA process has the potential to be a tool for their empowerment in addressing structural power inequities. For such a repositioning of SA, it is critical to focus not only on the technicality of generating evidence but also on the framework driving such a process, the mode of evidence generation and deployment, and integration into the organizational strategy. Such a process can be equally empowering, efficient in addressing the systemic challenges of increasing marginalized community's access to health care services, and valuable in sustaining those changes. The analysis of the strategies of JMS offers significant insights for researchers and practitioners working on SA and maternal health to re-articulate SA from the point of politics of empowerment of the marginalized communities.